Storytelling as A Medium For Prenatal Education (Munasabah Qs. An-Nahl 78) - Indah Istiqomah; Umu Intan Aulia; Sayyidah Rahmah Annabila; Rofiatul Hosna; Zohaib Hassan Sain (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
This article aims to provide knowledge about the importance of stimulating the fetus in the womb in accordance with the Qur'anic verse An-Nahl 78 regarding the creation of hearing that precedes the creation of the senses of sight and heart (reason and mind). In examining the verse, the researcher used the science of munasabah to analyze the relationship and harmony between An-Nahl 78 and other verses. The results are then correlated with medical facts and scientific journals in previous studies. Using books, journals, articles, and written documents as the main materials, this study employs a qualitative method. The results show that maximizing hearing during storytelling activities while the child is in the womb can stimulate their brain development and language skills. In line with Surah An-Nahl verse 78, this activity is also a concrete action to support the government in improving literacy through the National Literacy Movement (GLN) at the smallest level, namely the family.